Strategic management practices and financial performance: an exploratory study of small businesses in Terengganu / Mohd Rafi Yaacob and Syed Ihsan Syed Adam Aljafri - Yaacob, Mohd Rafi; Syed Adam Aljafri, Syed Ihsan (2002)
This study is based upon a pilot test conducted on small entrepreneurs during a Financial Management course conducted at Yayasan Pembangunan Usahawan, Kuala Terengganu on May 2000. The purpose of this research is to study the relationship between strategic management practices of small businesses and the impact on their financial performance. The interrelationship between entrepreneur characteristics, entrepreneur objectives, business environment, strategic management practices adopted and financial performance were analysed. Samples were analysed using reliability analysis, cross tabs, correlation and regression. The result shows that generally there is no significant relationship between financial performance and strategic management performance adopted by small businesses. However, entrepreneur characteristics were found to have a significant relationship with business strategies in comparison to entrepreneur objectives. Among the small businesses, government contractors were found to utilise low supplier bargaining power to obtain cheaper source of finance. Other interesting findings include strong emphasis on planning strategies by high financial performers. While average financial performers tend to focus on aggressive marketing strategies and Porter's generic strategies.